Ayurvedic Management on Manoavsada (Depression): Case Report (International Journal of Ayurveda and Pharma Research, 2022)
Among all the psychological disorders, depression is the most common mental disorder nowadays. According to WHO, approximately 280 million people have depression worldwide. In Ayurvedic classics Vishada and Avasada are the two mentioned conditions which have close resemblance with depression. Acharaya Charak quote “Vishado Rogavardhanam” i.e., it is the most foremost factor to worsen the condition of any disease. It comes under one of the eight Vataja nanatmaja vikaras which indicate that it cannot occur without the involvement of Vata dosha.In modern science there are enormous drugs for treatment of mental disorders but with so many adverse effects. The prolong consumption of these medications leads the patient more dreadful condition which became fatal at later stage. Acharya charak has quoted the definition of best treatment in Charak Samhita. He explains that the treatment that cures any diseases without causing any morbid condition or side effect said to be the best treatment. In this case study we try to explain the impact of Satvavjyachikitsha along with Samshaman and other Panchkarma procedures as given in the patient. The result came out as an eye opener about the experience made in this case without any side effects.